PERBANDINGAN KEDALAMAN DAN MATERIAL PERANGKAP POST LARVA LOBSTER DI TELUK AWANG, LOMBOK - Wahbi Wahbi; Mulyono S. Baskoro; Didin Komarudin (Jurnal Teknologi Perikanan dan Kelautan, 2023)
The rearing activities of lobster post-larvae still depend on seeds from nature, while the post-larvae caught are few and the size is not uniform. Therefore, effective and efficient fishing gear is needed. Regarding the effectiveness of fishing gear, it is influenced by various factors including the depth of operation and the forming material to obtain an effective and efficient trap, it was tested based on the constituent materials, namely cement sacks and shrimp feed sacks. At the depth of operation with a depth of 2, 4, 6, 8, 10, 12, and 14 m. This study aims to compare the effective trap materials for catching lobster post larvae and identify the appropriate depth of trap placement with the lobster post-larva swimming layer. The results showed that the comparison of the depth of the trap at a depth of 14 m gave the highest catch of 47 fish and the lowest at a depth of 2 and 4 m with a catch of 3 fish, while in the comparison of forming materials the highest catch was in the sack material, which was 191 individuals, while in the feed sack shrimp is 188 individuals. Based on the results of the study showed a depth of 14 m and cement sack material gave the highest catch.